Integrated Grain and Forage Rotations - J. D. Holman; A. Obour; T. Roberts; S. Maxwell (Kansas Agricultural Experiment Station Research Reports, 2018)
Interest in growing forages and reducing fallow has necessitated research on soil, water, and crop yields in intensified grain/forage rotations. Fallow stores moisture, which helps stabilize crop yields and reduces the risk of crop failure; however, only 25 to 30% of the precipitation received during the fallow period of a no-till wheat-sorghum-fallow rotation is stored. . The remaining 75 to 70% precipitation is lost, primarily due to evaporation. Moisture storage in fallow is more efficient earlier in the fallow period, when the soil is dry, and during the winter months when the evaporation rate is lower. It may be possible to increase cropping intensity without reducing crop yields by using forage crops in the rotation. This study evaluated integrated grain/forage rotations compared to traditional grain-only crop rotations.
Keywords: grain; forage; crop rotations; soil water